2014
DOI: 10.2298/gensr1403719r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of a Serbian grapevine germplasm collection based on morphoagronomic characteristics

Abstract: The objective of this study was to evaluate diversity and relationships among grapevine cultivars from the Serbian gene bank in Sremski Karlovci, and to identify the most useful variables for discrimination. A total of 54 grapevine cultivars have been studied. During the period 2000-2005, twelve quantitative and qualitative characteristics were evaluated using OIV categories to each trait. Characterization was done using multivariate statistical analyses: cluster and principal component analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Today, there are three major ampelographic collections for the Vitis genus in the Serbian plant gene bank: i) Sremski Karlovci, an experimental vineyard within the University of Novi Sad's Faculty of Agriculture containing a total of 737 samples, ii) Radmilovac, an experimental vineyard within the University of Belgrade's Faculty of Agriculture containing a total of 659 samples, and iii) The Centre for Viticulture and Wine Production at Niš containing a total of 336 samples (Nikolić et al, 2021). Results obtained by several authors (Rakonjac et al, 2014;Štajner et al, 2014) have confirmed high levels of diversity among cultivated varieties.…”
Section: Introductionmentioning
confidence: 63%
“…Today, there are three major ampelographic collections for the Vitis genus in the Serbian plant gene bank: i) Sremski Karlovci, an experimental vineyard within the University of Novi Sad's Faculty of Agriculture containing a total of 737 samples, ii) Radmilovac, an experimental vineyard within the University of Belgrade's Faculty of Agriculture containing a total of 659 samples, and iii) The Centre for Viticulture and Wine Production at Niš containing a total of 336 samples (Nikolić et al, 2021). Results obtained by several authors (Rakonjac et al, 2014;Štajner et al, 2014) have confirmed high levels of diversity among cultivated varieties.…”
Section: Introductionmentioning
confidence: 63%
“…In the present study, ANOVA, principal components, and genetic marker analyses were used to identify and classify the varietal diversity of the EVEGA Grapevine Germplasm Bank. Ampelographic descriptions, together with the identification of plant material using DNA markers, are the first steps in the characterization of grapevine germplasm collections (Muganu et al, 2009;Rakonjac et al, 2014;Zombardo et al, 2021). High diversity was found at a morphological level, as only 6 out of 74 ampelographic and ampelometric parameters studied were homogeneous for all varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Although modern viticultural production imposes the need to create better grapevine varieties, their spreading and propagation in nurseries is preceded by detailed verification, comprehensive assessment of value, and finally official recognition and their inclusion on the List of varieties and hybrids of agricultural and forest plants of the Republic of Serbia. RAKONJAC et al (2014) state that morphological classifications provide useful guidelines to variety relations, developing further insight for plant breeders and gene bank managers. The first step in this study is to ampelographically described existing varieties.…”
Section: Introductionmentioning
confidence: 99%